The Teacher’s Cognitive Role in the Efficiency of Distance Education: A Case Study - Kazana, Athina; Armakolas, Stefanos; Kazantzis, Savvas; Krotký, Jan (Social Education Research, 2022)
This paper aims to examine preservice teachers’ views of the School of Pedagogical and Technological Education (ASPAITE) regarding the skills of online teacher-counselors and the effectiveness of distance education during the COVID-19 pandemic. The aim of the study is related to a continuous research effort to ameliorate potential teachers’ effectiveness in distance education. Firstly, attention is drawn to the concept-key term of distance education, and afterwards, an extensive presentation of its basic principles and characteristics is provided: active teaching, leadership and management, active learning of students, and technological abilities. The results of the study show that the role of a teacher/counselor in distance education is a multiple one, as he or she must utilize and apply not only formal and informal qualifications as used in conventional education but also additional ones that bridge the gap caused by physical absence.